(untitled) (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Social Media became a means for sharing ideas and emotions in a public forum and social media became a platform for common public to express their views on different socio-political issues as well as the recent protest happened in Tamil Nadu . In January 2017, we witnessed there were huge protest across Tamil Nadu supporting Jallikattu, a bull-taming traditional Tamil sport which was banned by Supreme Court of India. The messages were spread in different Social Networking Sites and Apps triggered people to participate in the Jallikattu protest. People used Social Media like Facebook, Twitter and WhatsApp to organise a huge protest. With this background this paper analyses the role of social media in Jallikattu protest. How to cite this article: Raj N. Analysis on the Role of Social Media in Jallikattu Protest. J Adv Res Jour Mass Comm 2018; 5(4): 59-65. DOI: https://doi.org/10.24321/2395.3810.201820